2016
DOI: 10.1007/978-3-319-44272-3_1
|View full text |Cite
|
Sign up to set email alerts
|

Early Geometrical Thinking in the Environment of Patterns, Mosaics and Isometries

Abstract: This survey confirms that one of the research trends in early geometrical reasoning has been a focus on creating a theoretical basis for research in this area. The main reason for the work on the theoretical foundations has been the fact that building geometrical concepts proceeds according to other regularities more than it takes place while building arithmetic knowledge. In this way, a broad research area was outlined. The first theory was created by Dina and Pierre Van Hiele (the Netherlands), but many on-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 24 publications
0
8
0
3
Order By: Relevance
“…Geometry is one of the best areas for a child to enter the world of mathematics. The geometrical world can be opened very early because geometrical knowledge correlates very well with children's natural cognition (Swoboda & Vighi, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Geometry is one of the best areas for a child to enter the world of mathematics. The geometrical world can be opened very early because geometrical knowledge correlates very well with children's natural cognition (Swoboda & Vighi, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Although research published in the 1990s showed benefits of students programming Logo in their learning of transformations, in particular symmetries [1] and, more recently, it has been showed that students learning in dynamic manipulative environments (either real or electronic) are more successful than those learning in static environments [2], there is a lack of research on the application of the newly available technologies in the teaching and learning of geometry [3], either as purely technological classes or blended learning [4]. Furthermore, the educational constraints to in person classes imposed by the pandemic of covid-19 give an added value to technological teaching and learning environments that can be used in virtual classrooms, so research on new electronic learning environments and blended environments is still necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Technological environments, like those based on DGS, have proved to be helpful to prevent or remove this kind of students' prototypical images when they are allowed to manipulate the axes of symmetry and get used to see them with any slope [16]. Then, although teaching and learning of isometries have not been frequently explored by mathematics education research [7], an interesting research direction is the design of technological environments where students can manipulate geometrical objects (in our case those related to symmetries) to gain experience and build on it a deep understanding of the related concepts and properties [2]. In this paper we present a teaching unit for symmetries implemented as an interactive e-book [17] that takes advantage of the possibilities of DGS played in computers and tablets.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations